Comorbidity and multimorbidity in patients with chronic hepatitis C - Ya. E. Saranskaya; L. M. Kiseleva; A. A. Sachek (Журнал инфектологии, 2022)
The aim of the study was to analyze comorbidity in patients who underwent a course of antiviral therapy for chronic hepatitis C with direct antiviral drugs.Materials and methods: 288 patients diagnosed with chronic hepatitis C with stages of liver fibrosis from F1 to F4 according to the METAVIR scale, various genotypes, who underwent antiviral therapy with direct antiviral drugs in the period from 2018 to 2021, were under observation, with an analysis of comorbid and multimorbid diseases.Results of the study: most often in these patients, regardless of gender and antiviral therapy regimen, lesions of the gastrointestinal tract were registered in the form of various inflammatory diseases, as well as non-alcoholic fatty liver disease. In second place in terms of frequency of occurrence, diseases of the endocrine system were diagnosed, primarily due to the development of metabolic syndrome, as well as damage to the thyroid gland, as an extrahepatic manifestation of chronic HCV infection. Slightly less marked diseases of the cardiovascular system. A relationship was found between the number of comorbid diseases and the body mass index, with an increase in which the stage of liver fibrosis progresses.Conclusions: The frequency of comorbidity and multimorbidity in patients with chronic HCV infection is significantly higher than in uninfected patients. Patients with chronic hepatitis C with advanced stages of liver fibrosis (F3 and F4 according to the MEVIR scale) with overweight and obesity of varying severity are characterized by the highest incidence of comorbidities. A variety of extrahepatic manifestations of chronic hepatitis C determine the polymorbid profile of the patient.